Vitamin D as a Key Modulator of Physical Performance and Injury Prevention: A Narrative Review - Nieczyporuk, Mateusz; Omidi, Amin; Łupicka, Aleksandara; Kielan, Aleksandara; Orzechowska, Paulina; Dziurdź, Aneta; Budziszewska, Gabriela; Okupniak, Alicja; Ziemba, Monika; Majewska, Katarzyna (Quality in Sport, 2026)
The role of vitamin D3 (cholecalciferol) as a key modulator of athletic performance has been the subject of a considerable number of studies for a number of years. Vitamin D3, functioning as a prohormone, exerts its effects on muscle tissue through the action of VDR receptors, thereby influencing the morphology of type II fibres and calcium metabolism. The present article focuses on the correlation between serum 25(OH)D3 concentration and explosive strength, aerobic threshold, and immune resistance in athletes. The analysis demonstrates that maintaining concentrations between 40 and 70 ng/ml is imperative for optimising regenerative processes and minimising the risk of fatigue fractures. Furthermore, the prevalence of deficiencies within the athlete population, in conjunction with the recommended supplementation protocols, should be duly noted.